MOTIVASI PETANI PADI SAWAH DALAM MENERAPKAN SISTEM TANAM BENIH LANGSUNG DI DESA LAMOMEA KECAMATAN KONDA KABUATEN KONAWE SELATAN - Nurfadilla Nurfadilla; Musadar Musadar; Suriana Suriana (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2023)
The planting system is a planting business on a plot of land by arranging the layout and sequence of plants over a certain period of time. Direct seed planting system (TABELA), this system has been tried by several farmers in Indonesia. As an effort to increase the carrying capacity of the land, the effort that must be made is to carry out innovative planting techniques by changing the habits of farmers in carrying out planting using the TABELA system. The purpose of this study, to find out: Farmers' motivation (intrinsic and extrinsic motivation) in implementing the direct seed planting system (TABELA) and and how do farmers implement the direct seed planting system (TABELA) in Lamomea Village. This research was conducted in Lamomea Village, Konda District, South Konawe Regency from March 2022 to October 2022 with 20 farmers as informants. Data analysis in this study used qualitative methods. The results showed that the motivation of lowland rice farmers in Lamomea Village included intrinsic motivation with indicators of needs and expectations, extrinsic motivation with indicators of family support and rewards. While the TABELA system for lowland rice in Lamomea Village at the stage of land preparation and planting is in the good category, in the seed preparation and care/maintenance stages it is in the sufficient category while in the harvest stage it is in the less category. It can be seen that the farmers in Lamomea Village need to improve the application of some of the TABELA systems like the other stages.